2011
DOI: 10.1016/j.jad.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the United States Air Force: Risk factors communicated before and at death

Abstract: Background: Over the last decade, suicide rates in the U.S. military have steadily increased, resulting in a call for suicide-related research with military populations. The present project aimed to describe and evaluate the communications (i.e., verbally and in suicide notes) of 13 suicide risk factors in the suicide death investigation files of 98 active duty U.S. Air Force (USAF) members. Methods: Two-hundred thirty-seven suicide death investigation files were coded. Ninety-eight decedents left suicide note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Cox et al. () provided further support for the applicability of the IPTS in military populations in their study of suicide decedents in the U.S. Air Force. Studying thematic commonalities in the suicide notes and final verbal communications of these decedents, they found that the psychological constructs of hopelessness, perceived burdensomeness, and thwarted belongingness were all themes evident in those who died by suicide.…”
Section: Conceptualizing Suicidal Ideationmentioning
confidence: 98%
“…Cox et al. () provided further support for the applicability of the IPTS in military populations in their study of suicide decedents in the U.S. Air Force. Studying thematic commonalities in the suicide notes and final verbal communications of these decedents, they found that the psychological constructs of hopelessness, perceived burdensomeness, and thwarted belongingness were all themes evident in those who died by suicide.…”
Section: Conceptualizing Suicidal Ideationmentioning
confidence: 98%
“…military members experience unique barriers to behavioral healthcare that jeopardize opportunities for intervention. In an evaluation of service members deployed to Iraq or Afghanistan, results indicated that only half of those in need of behavioral healthcare received treatment (Cox, 2011). Table 4 shows some of the most common barriers to mental health in the military population (Ramchand, 2011).…”
Section: Barriers To Mental Health Carementioning
confidence: 99%
“…Thwarted belongingness has been found to be associated with suicidal ideation in military samples (Bryan, 2011). It has also been found to be a common theme in suicide notes left by military personal who died by suicide (Cox et al, 2011).The second component of suicidal ideation in IPT is perceived burdensomeness. This domain consists of misperceptions of the individual that he or she is a burden to others around him/her, failing not only to make meaningful contributions to society, but also serving as a liability to others.…”
mentioning
confidence: 96%